PENGARUH EARNING PER SHARE DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - L. Tobing, Vargo Christian; Simatupang, Eva Malina; Efriyenty, Dian; Azmiana, Risca (LPPM Universitas Putera Batam, 2025)
The capital market is a meeting place between stock sellers (parties who need funds) and stock buyers (parties who invest in shares). This study was conducted with the aim of knowing the effect of earning per share and dividend policy on stock prices. The objects in this study are automotive and component companies listed on the Indonesia Stock Exchange. The research period is 2017 to 2021. The population in the study amounted to 13 companies. Sampling using purposive sampling method, namely by setting criteria for research. The samples used in this study were 7 companies. The analysis methods that will be used in this study are: descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis and hypothesis testing; partial test (t test) and simultaneous test (F test). The results stated that earning per share and dividend policy partially and simultaneously had a significant effect on stock prices